Effect of exposure to 15% oxygen on breathing patterns and oxygen saturation in infants: interventional study - Parkins, K J (BMJ Group, 1998)
Objective: To assess the response of healthy infants to airway hypoxia (15% oxygen in nitrogen). Design: Interventional study. Settings: Infants’ homes and paediatric ward. Subjects: 34 healthy infants (20 boys) born at term; mean age at study 3.1 months. 13 of the infants had siblings whose deaths had been ascribed to the sudden infant death syndrome. Intervention: Respiratory variables were measured in room air (pre-challenge), while infants were exposed to 15% oxygen (challenge), and after infants were returned to room air (post-challenge). Main outcome measures: Baseline oxygen saturation as measured by pulse oximetry, frequency of isolated and periodic apnoea, and frequency of desaturation (oxygen saturation ⩽80% for ⩾4 s). Exposure to 15% oxygen was terminated if oxygen saturation fell to ⩽80% for ⩾1 min. Results: Mean duration of exposure to 15% oxygen was 6.3 (SD 2.9) hours. Baseline oxygen saturation fell from a median of 97.6% (range 94.0% to 100%) in room air to 92.8% (84.7% to 100%) in 15% oxygen. There was no correlation between baseline oxygen saturation in room air and the extent of the fall in baseline oxygen saturation on exposure to 15% oxygen. During exposure to 15% oxygen there was a reduction in the proportion of time spent in regular breathing pattern and a 3.5-fold increase in the proportion of time spent in periodic apnoea (P<0.001). There was an increase in the frequency of desaturation from 0 episodes per hour (range 0 to 0.2) to 0.4 episodes per hour (0 to 35) (P<0.001). In 4 infants exposure to hypoxic conditions was ended early because of prolonged and severe falls in oxygen saturation. Conclusions: A proportion of infants had episodes of prolonged (⩽80% for ⩾1 min) or recurrent shorter (⩽80% for ⩾4 s) desaturation, or both, when exposed to airway hypoxia. The quality and quantity of this response was unpredictable. These findings may explain why some infants with airway hypoxia caused by respiratory infection develop more severe hypoxaemia than others. Exposure to airway hypoxia similar to that experienced during air travel or on holiday at high altitude may be harmful to some infants.